RT-PCR for confirmation of echovirus 30 isolated in Belém, Brazil - GOMES, Maria de Lourdes Contente (2015)
Echovirus (Echo) 30 or human enterovirus B is the most frequent enterovirus associated with meningitis cases. Epidemics and outbreaks of this disease caused by Echo 30 have occurred in several countries. In Brazil, Echo 30 has been isolated from sporadic cases and outbreaks that occurred mainly in the south and southeast regions. We used RT-PCR to examine Echo 30 isolates from meningitis cases detected from March 2002 to December 2003 in Belém, state of Pará, in northern Brazil. The patients were attended in a Basic Health Unit (State Health Secretary of Pará), where cerebrospinal fluid (CSF) was collected and stored in liquid nitrogen. Weekly visits were made by technicians from Evandro Chagas Institute to the health unit and samples were stored at -70ºC in the laboratory until use. HEp-2 and RD cell lines were used for viral isolation and neutralization with specific antisera for viral identification. RNA extraction was made using Trizol reagent. The RT-PCR was made in one step, and the total mixture (50 µL) was composed of: RNA, reaction buffer, dNTP, primers, Rnase inhibitor, reverse transcriptase, Taq polymerase and water. The products were visualized in agarose gel stained with ethidium bromide, visualized under UV light. Among the 279 CSF samples examined, 30 (10.7%) were EV positive, 29 being Echo 30 and one was Cox B. Nineteen Echo 30 were examined with RT-PCR; 18 tested positive (762 and 494 base pairs). The use of this technique permitted viral identification in less time than usual, which benefits the patient and is of importance for public-health interventions.